E-yearbook of Food and Natural Resource Statistics for 2020 : Statistical facts on agriculture, forestry, fisheries and hunting in Finland - (:unkn) unknown (Natural Resources Institute Finland (Luke), 2021)
The Natural Resources Institute Finland (Luke) produces the majority of statistics concerning the Finnish agriculture and food processing industry, the forest sector, and the fisheries industry. The E-yearbook of Food and Natural Resource Statistics presents key figures for the 2019 statistical year. This and previous e-yearbooks are available on Luke’s statistics portal at stat.luke.fi/en/. The online service and the statistical database provide users with access to up-to-date background data and statistics. A printed version can be ordered via Luke’s online shop. The English version of the e-yearbook will be published in the spring of 2021. Without the reporting enterprises and their data, it would not be possible to compile the statistics. The statistics and data used in the e-yearbook are produced as a joint effort of the entire staff of Luke’s statistical services, and a large number of other experts from different fields have also participated in the compilation of this publication.
Keywords: natural resources; agriculture; forestry; bioeconomy; fisheries; hunting; statistics (data)